Grid integration of solar PV for multi-apartment buildings - Kozarcanin, Smail; Andresen, Gorm Bruun (International Journal of Sustainable Energy Planning and Management, 2018)
Several studies show that large installations of rooftop solar PV in residential low voltage grids, typically with many single family dwellings, may cause overvoltage issues during mid-day when local consumption is low and solar PV electricity generation high. Different so-called smart grid technologies, which often requires additional control, communication and monitoring equipment have been suggested to alleviate these and related problems. In this paper, solar PV integration is studied in the context of multi-apartment buildings where the rooftop potential is significant. To this end, the medium voltage grids of two multi-apartment areas, Bärnstenen and Alabastern in Vaxjö, Sweden are used as study cases. For these areas, it is found that active smart grid control or the introduction of new controllable load is not required. This finding applies to cases with very large solar PV installations corresponding to full coverage of the available rooftops and an annual yield corresponding to about eight times the annual electricity consumption. The conclusion is that multi-apartment residential areas may be ideally suited for large-scale solar PV installations without the need for smart grid infrastructure. These findings are contrary to, but not in disagreement with previous findings for low voltage residential grids.